Integrasi Teknologi Digital dalam Pembelajaran Biologi: Analisis Kualitatif terhadap Pemahaman Konseptual dan Keterampilan Abad 21 - Nofamataro Zebua (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology has brought significant changes in various aspects of life, including education. In biology learning, digital technology offers innovative solutions to overcome challenges in understanding abstract concepts, increase learning motivation, and develop 21st century skills. Interactive simulations, augmented reality (AR), virtual reality (VR) and online learning platforms allow students to visualize complex biological concepts, such as photosynthesis and DNA replication, more clearly and deeply. In addition, the integration of digital technology can improve students' critical thinking skills, creativity, collaboration and digital literacy. However, the implementation of digital technology in biology learning faces various challenges, including limited infrastructure, access gaps between urban and rural schools, and lack of training for educators. This study aims to explore the impact of digital technology on students' conceptual understanding and 21st century skills, and identify the main barriers to its implementation. The results of this study are expected to provide recommendations for the development of more effective and innovative biology learning strategies in the digital era